140k views
2 votes
Simplify 6 to the negative 3rd power over 6 to the 5th. 68 6−2 1 over 6 to the 8th power 1 over 6 to the 2nd power

User Daryl Teo
by
4.2k points

2 Answers

5 votes

Answer:

The simplified expression is given by:

1 over 6 to the 8th power.


(1)/(6^8)

Explanation:

We are asked to simplify the expression:

6 to the negative 3rd power over 6 to the 5th power.

which is mathematically written as:


(6^(-3))/(6^5)

Now, we know that:


(a^m)/(a^n)=(1)/(a^(n-m))

Here,


m=-3\ and\ n=5

Hence, we get:


(6^(-3))/(6^5)=(1)/(6^(5-(-3)))

i.e.


(6^(-3))/(6^5)=(1)/(6^(5+3))

Hence, we get the simplified expression as follows:


(6^(-3))/(6^5)=(1)/(6^8)

User Dkatzel
by
3.9k points
0 votes

Answer:


(1)/(6^8)

Explanation:


(6^(-3))/(6^5)=(1)/(6^(5+3))=(1)/(6^8)

___

The applicable rules of exponents are ...


a^(-b)=(1)/(a^b)\\\\a^b* a^c=a^(b+c)

User Chris Marie
by
4.6k points